Rhodium-Catalyzed Oxidative Coupling of Aryl Hydrazones with Internal Alkynes: Efficient Synthesis of Multisubstituted Isoquinolines - Liu, Wenting; Hong, Xiaohu; Xu, Bin (Synthesis, 2013)
An efficient rhodium-catalyzed oxidative coupling reaction has been developed that gives high yields of multisubstituted isoquinolines from easily accessible aryl hydrazones and internal alkynes. Indenone hydrazone can also be synthesized in high yield from the corresponding benzaldehyde hydrazone by using this approach.
Keywords: alkynes; cyclization; hydrazones; heterocycles; rhodium; catalysis